IMPLEMENTATION OF THE PRINCIPLES OF ACADEMIC INTEGRITY IN THE CONTEXT OF EUROPEAN PRACTICE - Batechko, Nina; Durdas, Alla; Kishchak, Tetyana; Mykhailichenko, Mykola (Educological discourse, 2020)
The article deals with the main challenges which the student community and teaching staff face towards building a European-style university based on the principles of academic integrity as a component of higher education quality. The basic universal norms, which should enter into the daily life of the university and ensure the improvement of the quality of educational and scientific process, have been considered in the article; the basic manifestations of academic dishonesty have been highlighted; the experience of the EU and of France in particular, in implementation of academic integrity principles in the life and activities of students and teachers has been considered. The main method of overcoming academic dishonesty by the developed countries has been mentioned. The respect of academic integrity principles as a component of higher education quality has been stressed. The current state of the principles of academic integrity implementation in the Ukrainian university education has been noted. The notion and principles of academic integrity have been stated. The types of academic dishonesty have been revealed. Academic integrity as a set of ethical principles and rules defined by the Law of Ukraine «On Education» has been mentioned in the article. The initiatives taken in the world to overcome the problem, have been revealed. The chronology of the advances in this field has been provided in the article. The European Union-funded project on the «Comparison of policies for academic integrity in higher education across the European Union» has been revealed in the article as an important initiative of the EU countries in academic integrity principles implementation. The aim, the participants and the target group of this project have been highlighted. It was stressed that the establishment of the principles of academic integrity is quite a complicated process that involves not only the definition, fixation, but also the conscious and free adoption of these principles by all members of the academic community. The presence of goodwill, enlightenment of enthusiasm, confidence in one’s rightness among adherents of academic integrity, combined with modern information technologies allow to accelerate this process in time and expand the circle of ideological supporters of these principles.